2021
DOI: 10.1007/s11910-021-01134-x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Diagnostic Workup Following Traumatic Spinal Cord Injury: Advances in Biomarkers

Abstract: Purpose of Review Traumatic spinal cord injury (SCI) is a life-changing event with drastic implications for patients due to sensorimotor impairment and autonomous dysfunction. Current clinical evaluations focus on the assessment of injury level and severity using standardized neurological examinations. However, they fail to predict individual trajectories of recovery, which highlights the need for the development of advanced diagnostics. This narrative review identifies recent advances in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 101 publications
2
12
0
Order By: Relevance
“…However, it is not always available in some patients, especially when they are unresponsive or obtunded and those with penetrating metal injuries (Elizei and Kwon, 2017). Previous Frontiers in Pharmacology frontiersin.org studies have pointed out the use of some biomarkers in peripheral blood can be a key and stable predictor of acute SCI (Tigchelaar et al, 2019;Schading et al, 2021). In this study, we analyzed a peripheral blood RNA-seq cohort after SCI (GSE151371), including an RNA expression profile and clinical information.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not always available in some patients, especially when they are unresponsive or obtunded and those with penetrating metal injuries (Elizei and Kwon, 2017). Previous Frontiers in Pharmacology frontiersin.org studies have pointed out the use of some biomarkers in peripheral blood can be a key and stable predictor of acute SCI (Tigchelaar et al, 2019;Schading et al, 2021). In this study, we analyzed a peripheral blood RNA-seq cohort after SCI (GSE151371), including an RNA expression profile and clinical information.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of primary and secondary damage to the spinal cord, some molecules appear in CSF, which is considered as a cardinal sign of disintegration of cells and extracellular matrix in the immediate impact area. CSF biomarkers are used as tools in assessing severity, prognosis, and treatment and rehabilitation regimes of patients with SCI [102,103]. Damage biomarkers reflect the degree of involvement in the pathological process of the entire organ along the rostro-caudal axis.…”
Section: Bioactive Molecules and Biomarkers In Csfmentioning
confidence: 99%
“…At the molecular level, pioneering work by Kwon et al demonstrated the predictive utility of several proteins (these being either cytokines or intracellular proteins) in the cerebrospinal fluid (CSF) of SCI patients as candidate biomarkers for detecting local inflammation and tissue destruction at the lesion site [ 9 , 31 , 32 ▪▪ ]. A significant number of other studies have also described links between nontraditional biomarkers of injury and neurological recovery from SCI, with varying strengths of association and clinical utility (reviewed in detail in [ 9 , 33 ]). However, none of these have as of yet been accepted and incorporated into routine clinical practice [ 22 ].…”
Section: Emerging Molecular Biomarkers For Stratification and Prognosis Of Spinal Cord Injurymentioning
confidence: 99%
“…Ultimately, the future of SCI prognostication lies in the development of highly sensitive biomarker panels that can provide a detailed general assessment of injury severity and temporal evolution of the lesion site, and also help facilitate selection of the right treatment option(s) as part of personalised medicine approaches to acute SCI. We envisage that immunological biomarkers will be used and integrated here with structural biomarkers of tissue damage (DAMPs), along with quantitative imaging methods that are in the pipeline for eventual clinical use [ 26 , 33 , 66 , 67 ], yielding an all-encompassing and empirically tested panel that can account for the complexity of SCI pathophysiology and patient heterogeneity (Fig. 1 ).…”
Section: Towards Better Diagnosis and Prognosis For Acute Spinal Cord Injury: The Road Aheadmentioning
confidence: 99%